The relationship between financial distress risk and stock returns: Evidence from Sri Lanka - Gimhan, L.D.N.; Anuradha, P.A.N.S. (University of Jaffna, 2022)
If financial foundation of the company is distressed and appears to be in bankruptcy, it can adversely affect all investors who are involved in business and financial partnerships with the company. As the main objective of this study, we have analyzed whether there is any significant difference between stock returns of a financially distressed company and non-distressed company. Altman Z-score model has been applied for measuring the financial distressed companies and categorization of companies in addition to the Multivariate Discriminate Analysis analytical technique. Data has obtained from 101 listed companies in Colombo stock exchange over a period of five years. From the 101 companies, 59 were identified as non-distressed and gray area firms, whereas 42 were categorized as financially distressed. The stock return has obtained for each company to check whether there is any significant difference between stock returns of a financially distressed company and financially non-distressed company. The results indicate that the financial distress risk is not affected to the stock return of the selected companies with the conclusion that there is not any significant difference between the stock returns of distressed companies over non-distressed companies. By looking individually and collectively at the return patterns of financially distressed and non-distressed companies, the study can be used effectively for successful decision-making for investors as well as corporate bodies when getting their investment decisions.
Keywords: Bankruptcy; Financial distress risk; Colombo stock exchange; Altman Z-score model; Stock returns